Persistence and activity levels of primitive reflexes in young high-level football players - Bastiere, Julie; Lussiana, Thibault; Young, Damien; Gindre, Cyrille; Mourot, Laurent (Frontiers in Sports and Active Living, 2024)
Introduction Primitive reflexes (PR) induce involuntary automatic movements in response to specific stimuli. This study aimed to determine the prevalence of active PR in young high-level football players. Methodology Sixty-nine national-level football players from a French academy were tested (17.0 ± 1.4 years; 69.6 ± 8.0 kg; 178.9 ± 6.9 cm) to evaluate the persistence of PR, following the methodology of the Institute for Neuro-Physiological Psychology (INPP) and the classification by a global score (GS). Based on the sum of seven tests, each was rated between 0 = null and 4 = max. The GS is classified into five categories from no activity to maximal (0–1 = no activity, 2–7 = low, 8–13 = medium, 14–21 = high, and 22–28 = maximal). Result Around two-thirds (68.1%) of players presented active PR at different activity levels. Among them, a small proportion (7.2%) had medium GS, while 60.9% had a low GS. The GS was not dependent on field position or the age of the players (p > 0.05). However, playing football in an age category higher than their own was associated with significantly more active primitive reflexes (PR) compared to being in their age category (p < 0.01). The results showed that 72.7% of “upgraded” football players had low GS and 18.2% had medium GS, compared to 55.3% and 2.1% in the non-upgraded group. Discussion The findings of the current study demonstrate that PR could still be active in a healthy population of high-level football players. Practicing a single sport for years and upgrading players could create a negative environment that can ultimately lead to the activation of otherwise integrated PR.